OUTCOMES OF INVASIVE FUNGAL RHINOSINUSITIS EXTENDING ADJACENT AREA- A CLINICO-RADIOLOGICAL IMPLICATIONS - Anish Kumar; Avneesh Kumar; Sonali Bandil; Saket Gupta (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Invasive fungal rhinosinusitis (IFRS) is an aggressive, life-threatening disease that primarily affects immunocompromised patients and can rapidly extend into adjacent anatomical structures, such as the orbit and cranial cavity. The clinical and radiological implications of this extension have profound impacts on patient outcomes, often increasing morbidity and mortality. This study aims to investigate the clinical outcomes and radiological features of IFRS when it extends to adjacent areas, focusing on the correlation between early detection, imaging findings, and treatment strategies. Our analysis reveals that early recognition through imaging, followed by aggressive surgical intervention and antifungal therapy, is crucial to improving survival rates, though outcomes remain poor in cases involving orbital or intracranial extension. A comprehensive review of case studies, alongside radiological data, offers new insights into the management and prognosis of patients with advanced IFRS.